Is It Time to Explore the Health Policy Process Within Governance and Health Systems Frameworks?; Comment on "Modelling the Health Policy Process: One Size Fits All or Horses for Courses?" - Stephen Peckham (Kerman University of Medical Sciences, 2023)
There is clearly a need to improve the use of more robust policy theory on health policy analysis. Powell and Mannion in an editorial on the relationship between health policy analysis and the wider field of public policy theory note, as others have done before, the limited application of policy theory in health policy analysis. However, they also highlight that within the health policy analysis arena new models have emerged which have wider use within policy analysis such as the health policy triangle. While Powell and Mannion suggest that health policy analysis can take one of two paths I argue that we should be developing more integrated frameworks of health policy processes, governance and systems which would involve the use of robust public policy theories and models.